Lipid nanocarriers for anti-HIV therapeutics: A focus on physicochemical properties and biotechnological advances - Faria, MJ (2021)
Since HIV was first identified, and in a relatively short period of time, AIDS has become one of the most devastating infectious diseases of the 21st century. Classical antiretroviral therapies were a major step forward in disease treatment options, significantly improving the survival rates of HIV-infected individuals. Even though these therapies have greatly improved HIV clinical outcomes, antiretrovirals (ARV) feature biopharmaceutic and pharmacokinetic problems such as poor aqueous solubility, short half-life, and poor penetration into HIV reservoir sites, which contribute to the suboptimal efficacy of these regimens. To overcome some of these issues, novel nanotechnology-based strategies for ARV delivery towards HIV viral reservoirs have been proposed. The current review is focused on the benefits of using lipid-based nanocarriers for tuning the physicochemical properties of ARV to overcome biological barriers upon administration. Furthermore, a correlation between these properties and the potential therapeutic outcomes has been established. Biotechnological advancements using lipid nanocarriers for RNA interference (RNAi) delivery for the treatment of HIV infections were also discussed.